Magnetic studies of the Late Cretaceous magmatism in Portugal : from Iberian plate kinematics to magnetic fabrics - Neres, Marta (2014)
Tese de doutoramento (co-tutela), Ciências Geofísicas e da Geoinformação (Geofísica), Université de Toulouse, Universidade de Lisboa, 2013